A Framework with reduced computational burden for Seismic Fragility Assessment of Reinforced Concrete Buildings in High-Intensity Seismic Zones. (October 2021) - Zain, Muhammad; Usman, Muhammad; Hassan Farooq, Syed
Highlights: This paper provides a new methodology for developing analytical fragility curves. The developed fragility curves incorporate effect of higher modes while using IDA. With presented methodology, fragility curves can be developed for individual mode. Modal vulnerability results can be combined to develop total seismic vulnerability. Presented framework substantially reduces computational time with accurate results. Abstract: The current research is targeted to develop the analytical fragility relationships of reinforced concrete (RC) buildings in high-intensity seismic zones by considering the effects of higher structural modes to reduce the computational effort. A new framework is presented in the study to assess the vulnerability in terms of the fragility relationships that can consider the modal response of individual modes in a building structure. The developed methodology considers the uncoupled modes of a structure employing a nonlinear single degree of freedom structures and defines distinct limit states for each mode separately. By using the presented methodology, the response of higher modes can be incorporated in the fragility assessment. For elucidation, a two-story reinforced concrete (RC) school building structure is selected from seismic zone 4 of Pakistan. In the first place, its vulnerability is assessed by developing fragility relationships using dynamic response history analysis of full three Dimensional nonlinear analytical models, subsequently, the fragility relationships are developed using the presented methodology by considering the first two modes of the structure. Afterward, a comparison has been made between the developed fragility curves from both of the methodologies. The results prove the effectiveness, swiftness, and the simplicity of the established methodology for carrying out the vulnerability assessments without compromising any accuracy. The developed framework reduces the computational time of one calculation cycle from 72 h for conventional methods to merely 4 h using a regular computer.